2017
DOI: 10.1016/j.bmc.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and evaluation of A-ring-modified lamellarin N analogues as noncovalent inhibitors of the EGFR T790M/L858R mutant

Abstract: A series of A-ring-modified lamellarin N analogues were designed, synthesized, and evaluated as potential noncovalent inhibitors of the EGFR T790M/L858R mutant, a causal factor in the drug-resistant non-small cell lung cancer. Several water-soluble ammonium- or guanidinium-tethered analogues exhibited good kinase inhibitory activities. The most promising analogue, 14f, displayed an excellent inhibitory profile against the T790M/L858R mutant [IC (WT) = 31.8 nM; IC (T790M/L858R) = 8.9 nM]. The effects of A-ring-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
(63 reference statements)
4
17
0
Order By: Relevance
“…In contrast to osimertinib, Lam14 maintained its efficacy against EGFR del ex19/T790M/C797S at a similar level to its inhibitory activity against EGFR del ex19/T790M (Figure 4B,C). Lam14 potently inhibits the activation of the mutant EGFR kinase in comparison WT EGFR kinase in vitro 38 . The Ba/F3 model also showed that mutant EGFR del ex19/T790M/C797S is more sensitive to Lam14 than WT EGFR (Figure 4C,D).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast to osimertinib, Lam14 maintained its efficacy against EGFR del ex19/T790M/C797S at a similar level to its inhibitory activity against EGFR del ex19/T790M (Figure 4B,C). Lam14 potently inhibits the activation of the mutant EGFR kinase in comparison WT EGFR kinase in vitro 38 . The Ba/F3 model also showed that mutant EGFR del ex19/T790M/C797S is more sensitive to Lam14 than WT EGFR (Figure 4C,D).…”
Section: Resultsmentioning
confidence: 88%
“…Modifying the A‐ring of LamN altered target orientation and inhibited the EGFR T790M/L858R mutant at a low nanomolar IC 50 in vitro (8.9 nM) 38 . To examine the target transition among lamellarin derivatives at the cellular level, two bioinformatic approaches were adopted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl 5-(2,2-difluorobenzo[d] [ 1 , 3 ] dioxol-5-yl)-1H-pyrrole-2-carboxylate ( 2u ) The general Suzuki procedure B was applied to methyl 5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1 H -pyrrole-2-carboxylate (251 mg, 1 mmol, 1 equiv) and 5-bromo-2,2-difluorobenzo[d] [ 1 , 3 ]dioxole (204 µL, 356 mg, 1.5 mmol, 1.5 equiv) for 48 h. Colorless solid; yield: 224 mg (80%); mp 171–173 °C; R f = 0.30 (hexanes–CH 2 Cl 2 1:3). FT-IR (ATR): 3315, 3142, 2961, 1680, 1619, 1514, 1472, 1441, 1387, 1288, 1241, 1060, 1044, 1003, 964, 938, 826, 765, 704, 634 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…5-Aryl 1 H -Pyrrole-2-carboxylate esters constitute an important class of pyrrole derivatives [ 1 , 2 ]. This structural motif is present in several natural products and their analogs such as Lamellarins [ 3 , 4 , 5 , 6 , 7 ] (topoisomerase I inhibitor, MDR reversal agent, and anti-HIV agent), and arylated hymenialdisine [ 8 , 9 ] (ChK2 inhibitor), as well as in several other biologically active compounds with anti-HIV [ 10 , 11 , 12 , 13 , 14 ], antibacterial [ 15 ], antimitotic [ 16 ], and cytotoxic [ 17 ] activities ( Figure 1 ). 5-Aryl 1 H -Pyrrole-2-carboxylate esters and their derivatives have also found applications, for example, as organic fluorescent materials [ 18 , 19 ], anion receptors/molecular logic gates [ 20 ], and as building blocks for metal organic frameworks [ 21 ] and helical asymmetric architectures [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%